Metabolite and water apparent diffusion coefficients in the isolated rat heart: effects of ischemia. - Liess, C; Radda, G; Clarke, K (2000)
A decrease in the apparent diffusion coefficient (ADC) of water is important in the detection of acute brain disorders, yet it is unknown whether changes in myocardial ADCs hold similar potential. Consequently, in this study a STEAM pulse sequence was modified in order to measure the ADCs of water and the (1)H-NMR detectable metabolites, taurine (an inert marker) and creatine, during perfusion, ischemia, and reperfusion in the isolated rat heart. At the short diffusion time of 50 ms, myocardial ADCs were (1.06 +/- 0. 07) x 10(-3) mm(2)/s for water, (0.29 +/- 0.01) x 10(-3) mm(2)/s for taurine and (0.26 +/- 0.01) x 10(-3) mm(2)/s for creatine. Heart water and taurine ADCs remained constant during ischemia, yet the total creatine ADC increased by 35% owing to the hydrolysis of PCr to creatine. The average cardiomyocyte diameter, calculated from taurine ADC values measured at diffusion times between 50 ms and 1510 ms, was 40 microm in the perfused heart and 27 microm by the end of ischemia. It is concluded that the taurine ADC measured at short diffusion times does not reveal ischemic injury in the heart, but at long diffusion times may be used to calculate changes in myocyte diameter. Magn Reson Med 44:208-214, 2000.